The influence of board of directors' characteristics on dividend distribution policies in Jordanian public shareholding companies - Aleqab, Mahmoud Mohmad; Al-Zu'bi, Thikryat Abdul Sattar (International Journal of Innovative Research and Scientific Studies, 2025)
This research explores how specific attributes of corporate boards affect dividend policy among listed companies in Jordan. Drawing on data from 77 non-financial firms listed on the Amman Stock Exchange between 2015 and 2023, the study evaluates the impact of five core board characteristics: board size, board ownership, political connections, board independence, and gender diversity on dividend policy. A panel data regression model was employed to assess these relationships. The analysis revealed statistically significant positive effects of these governance features on dividend payout ratios. Additionally, liquidity and leverage demonstrated considerable influence, while firm size had no meaningful impact. The findings highlight the importance of board structure in shaping equitable dividend policies and offer practical implications for enhancing governance practices in emerging markets.